Strategi Peningkatan Penjualan Koperasi RSU Muhammadiyah Ponorogo Melalui Analisis Perilaku Konsumen, Preferensi Produk, Dan Service Quality Terhadap Pelanggan - Melynda Risma Nahria; La Ode Sugianto (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract: The Muhammadiyah Ponorogo Regional Hospital Cooperative plays a strategic role in supporting the welfare of its members and meeting the practical needs of customers within the hospital environment. However, the dynamics of consumer behavior, variations in product preferences, and demands for quality service require the cooperative to continuously adapt. This article aims to analyze sales increase strategies through consumer behavior, product preferences, and service quality approaches. The methods used are independent work based on field observations, sales data analysis, and evaluation of implemented work programs, including monthly product promotions, routine evaluation management, and optimization of the Year-End Meeting (RAT). The results show that the implementation of monthly promotions increased sales volume, evaluation management improved service performance, and optimization of the RAT increased member participation and loyalty. This integrated strategy has proven effective in driving sustainable sales growth for the cooperative.